STRATEGI PENGEMBANGAN MOTORIK HALUS DAN KASAR ANAK USIA DINI MELALUI KEGIATAN BERMAIN TERSTRUKTUR - Jf, Nurul Zahriani; Mahrani, Nana (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This study aims to examine the implementation of play strategies that are systematically designed to support the development of fine and gross motor abilities in early childhood. The focus of this study departs from the urgency of providing directed motor stimulation as an important part of supporting the process of holistic child development. This research uses a qualitative method with a case study approach. The choice of this approach aims to allow the researcher to conduct an in-depth exploration of the systematically designed play strategies that support the development of fine and gross motor skills in early childhood. Data collection techniques through direct observation, documentation of children's activities, and interviews with teachers at TK IT ZIA Salsabila, Medan. Participants in this study included 15 children in group B and the class teacher as the main source of information. The findings show that activities such as coloring, cutting and folding paper can hone visual-motor coordination and make fine movements. Meanwhile, physical games such as rhythmic gymnastics and ball throwing and catching proved to train children's muscle strength, body balance, and courage. Strategic planning by teachers, effective interactions, and the support of an optimal learning environment are important elements of the success of this activity. Teachers are advised to continue developing a variety of structured educational games and implement portfolio assessment as an authentic child development evaluation tool.